PERAN MODAL SPIRITUAL DALAM PEMBENTUKAN BUDAYA AMARE DI KALANGAN MAHASISWA STIM SHANTI BHUANA: PERAN MODAL SPIRITUAL DALAM PEMBENTUKAN BUDAYA AMARE DI KALANGAN MAHASISWA STIM SHANTI BHUANA - eligia salfarini (Department of Management - Institut Shanti Bhuana, 2021)
ABSTRACT This study aims to describe the role of spiritual capital in the formation of culture Amare at student of STIM Shanti Bhuana. The paradigm of this research is qualitative and uses triangulation methods to maintain reliability. This study illustrates how the cultivation of values among students through spiritual formation, boarding life, campus life, and curriculum can produce spiritual capital in every student. Spiritual capital can be seen from the fruits produced, which are growing in faith, integrity, responsibility, dependability, having a spirit of altruism, intellectual enhancement, and professionalism. Beside of producing positive things among students, it turns out that this spiritual capital embodies the vision and mission of STIM Shanti Bhuana. The main thing that is the key to the formation of Amare Culture at student of STIMe Shanti Bhuana actually is the cultivation of spiritual values that forms spiritual capital. Keyword: Spiritual capital, Amare Culture, cultivation of spiritual values.